The Lived Experience of Male Junior High School Students with an Emphasis on Providing a Curriculum Model - Jamshidi, Hassan; Sa'adatmand, Zohreh; Keshti Arai, Narges (Iranian Journal of Educational Sociology, 2022)
Purpose: The primary objective of this study was to analyze the lived experiences of male first grade high school students regarding sex education with an emphasis on providing a curriculum model. Methodology: The method of the present study was qualitative-phenomenological and applied in terms of purpose. The statistical population of the study was the male high school students of Isfahan in the academic year of 2018-19, who were interviewed by semi-structured and in-depth interviews with 17 of them by purposeful sampling method until they reached theoretical saturation. Data analysis was performed at three levels of open, axial and selective coding. To validate the findings, the researcher and colleagues first reviewed the entire coding process and then provided it to 6 professors and experts. Satisfactory and approved. Findings: The findings were classified into two main categories which are: “Objectives” and “Content”. Regarding the “Objectives” group, 4 main components (being familiar with the type of dressing and hijab, sexual recognition, responsibilities related to sexual functions, and prevention of sexual deviations) and 18 sub-components in terms of the content of the curriculum based on sexual education, 6 components (reproduction, sexual relationships, sexual maturity, sexual abuse, sexual health, and sexual information references) and 23 sub-components were obtained. Conclusion: According to the present data, it may be stated that based on the students' viewpoint, recognizing sexual issues is considered to be a need that should be adequately addressed and understood during the educational period at school.